Upper airways colonisation of Streptococcus pneumoniae in adults aged 60 years and older: A systematic review of prevalence and individual participant data meta-analysis of risk factors. Issue 4 (October 2020) - Smith, Emma L.; Wheeler, India; Adler, Hugh; Ferreira, Daniela M.; Sá-Leão, Raquel; Abdullahi, Osman; Adetifa, Ifedayo; Becker-Dreps, Sylvia; Esposito, Susanna; Farida, Helmia; Kandasamy, Rama; Mackenzie, Grant A.; et al.
Highlights: Systematic review and meta-analysis of 18 studies and more than 6000 participants. Adults over the age of 60 had a pooled prevalence of pneumococcal carriage of 9%. Risk factors: contact with children, smoking and residing in a nursing home. Summary: Background: Colonisation with Streptococcus pneumoniae can lead to invasive pneumococcal disease and pneumonia. Pneumococcal acquisition and prevalence of colonisation are high in children. In older adults, a population susceptible to pneumococcal disease, colonisation prevalence is reported to be lower, but studies are heterogeneous. Methods: This is a systematic review and meta-analysis of prevalence of, and risk factors for, pneumococcal colonisation in adults ≥ 60 years of age (PROSPERO #42016036891). We identified peer-reviewed studies reporting the prevalence of S. pneumoniae colonisation using MEDLINE and EMBASE (until April 2016), excluding studies of acute disease. Participant-level data on risk factors were sought from each study. Findings: Of 2202 studies screened, 29 were analysable: 18 provided participant-level data (representing 6290 participants). Prevalence of detected pneumococcal colonisation was 0–39% by conventional culture methods and 3–23% by molecular methods. In a multivariate analysis, colonisation was higher in persons from nursing facilities compared with the community (odds ratio (OR) 230, 95% CI 126–421 and OR 772, 95% CI 115–5185, respectively), in those who were currently smoking (OR 169, 95% CI 112–253) or those who had regular contact with children (OR 193, 95%CI 127–293). Persons living in urban areas had significantly lower carriage prevalence (OR 043, 95%CI 027–070). Interpretation: Overall prevalence of pneumococcal colonisation in older adults was higher than expected but varied by risk factors. Future studies should further explore risk factors for colonisation, to highlight targets for focussed intervention such as pneumococcal vaccination of high-risk groups. Funding: No funding was required.